Green Turtle (Chelonia Mydas) Landings And Hatchlings Rate At Pangumbahan Turtle Conservation Area, Sukabumi - Umar Adisubroto; Togu Pardede (International Journal of Geotourism Science and Development, 2024)
Green Turtle, Chelonia mydas, or “penyu hijau” is an endangered species that can be found in the area of Geopark Ciletuh-Palabuhanratu, West Java. This Geopark has become the UNESCO Global Geopark since 2018. One location where the Green turtles can be found is Pangumbahan Beach, Ciracap District, Sukabumi Regency. The conservation management area is about 58.43 hectares while the length of the beach is about 2,300 m. Pangumbahan Beach’s geological characteristic is unique, consisting of specific sand called silica or quartz sand, whereas the coastline directly faces the Pacific Ocean. The important vegetation communities in the area are composed of herbs, shrubs, and some tree species. These factors make the beach the favorite nesting ground for turtles. However, some local communities still feed and sell turtle eggs, making them the favorite dish for religious offerings. During the past several years the number of turtles that nest and successfully hatch has decreased. Several factors are thought to cause this decline such as beach abrasion, the market for turtle eggs, and so on. The data of the turtle eggs collected from the beach and kept in the hatchery were examined. The number of eggs that successfully hatched was also studied. The study explains the relationship between the geological, cultural, and biodiversity aspects of the turtle nesting ground and the successful hatchlings rate